THE ROLE OF THE DIGITALIZATION OF LEARNING MEDIA ON THE QUALITY OF LEARNING - Bartolomeus Galih Visnhu Pradana; Yohanes Mario Pratama (Jurnal Sosial Humaniora, 2022)
The school functioned as a place to educate and forge students into complete individuals. Schools, through existing facilities, must be able to prepare students to be competent in the digitalization era. Efforts to improve the quality of learning during the current pandemic must be in the process of improving and updating the learning media used. This study aims to determine the role of digitalization of learning media on the quality of learning at SDN Bronggang Baru. The method used in this study is qualitative, with a focused interview approach carried out through several stages. The observations were made to obtain an initial picture regarding digitization at SDN Bronggang Baru. Based on these observations, a literature study was conducted to provide a theoretical analysis of digitalization in schools based on previous research and expert opinions. Data collection and processing are done based on the results of observations and literature studies that have been performed as well as the effects of focus group discussions. This research shows that the output of digitalization of learning media implemented at SDN Bronggang Baru positively impacts the quality of learning for the entire academic community in the school environment. Digitizing education makes the transfer of information easy and fast. Services to students can be maximized with the digitalization of this education. The digitalization of education can be the forerunner to realizing an intelligent school with an insight into the future.